MODERN EDUCATION AND INNOVATIVE TECHNOLOGIES IN PHYSICAL EDUCATION CLASSES - Mushtariy Razzakova (Journal Park Publishing, 2022)
In our time, physical education performs important social functions to optimize a person's physical condition, organize a healthy lifestyle and prepare for life practice. Today, it must shape not only the physical but also the intellectual and socio-psychological components of man. As in any field, physical education involves working with a person's spiritual world - his views, knowledge and skills, emotional attitudes, values, worldviews. Modern conditions of development of our society require a different approach to the problem of formation of physical culture.
Keywords: physical culture; intellectual potential; non-traditional lessons